Arbuscular mycorrhizae of dominant plant species in Yungas forests, Argentina - Becerra, Alejandra Gabriela (2009)
In Argentina the Yungas forests are among the ecosystems most affected by human activity, with loss of biodiversity. To assess the arbuscular mycorrhizal (AM) colonization and the arbuscular mycorrhizal fungi (AMF) spore numbers in these ecosystems, the roots of the most dominant native plants (one tree, Alnus acuminata; three herbaceous, Duchesnea indica, Oxalis conorrhiza, Trifolium aff. repens; and one shrub, Sambucus peruviana) were studied throughout the year from two sites of Yungas forests. Assessments of mycorrhizal colonization (percent root length, intraradical structures) were made by washing and staining the roots. Soil samples of each plant species were pooled and subsamples were obtained to determine AM spore numbers. The herbaceous species formed both Arum- and Paris-type morphologies, whereas the tree and the shrub species formed respectively single structural types of Arum-and Paris-type. AM colonization, intraradical fungi structures and AMF spore numbers displayed variation in species, seasons and sites. D. indica showed the highest AM colonization, whereas the highest spore numbers was observed in the rhizosphere of A. acuminata. No correlation was observed between spore numbers and root length percentage colonized by AM fungi. Results of this study showed that Alnus acuminata is facultatively AM. The AM colonization, intraradical fungi structures and AMF spore numbers varied in species depending on phenological, climatic and edaphic conditions.